(untitled) (Tanzania Journal for Population studies and Development, 2022)
Understanding spatial-temporal land use and cover change is essential in developing physical planning strategies in populated and fast-growing towns and cities. This study examined the spatial and temporal changes in land use and land cover in West District in Zanzibar. Remote sensing techniques—including spatial and temporal assessment of land use and land cover changes between 1975 and 2015—were employed to establish the status and trend of land use and land cover changes in the district. Participatory field observation, focus group discussions and secondary data review were used in data collection. The study findings revealed that between 1975 and 2015 there were spatial and temporal changes in land use and land cover; with one land use and land cover type changing at the expense of another, and vice versa. Also, about 90% of settlements in the district developed at the expense of forest and agricultural lands, leading to rapid landscape changes of 83% in 40 years. At this pace, it is predicted that in the next 40 years the district’s built-up area may expand beyond its borders. Such changes are linked, among other factors, to increased population demanding more land for settlements among other domestic needs. This article concludes that land use and land cover in the West District, Zanzibar, depict notable quantitative and qualitative changes. Continuous land use and land cover change detection and modelling for future settings and planning are recommended for sustainable land management.